Answers

2014-11-05T12:07:05+08:00
Simple math.

There are several forms for this.

I'll use one for your question.

y – y1 = m(x – x1)

where,

(x1, y1) = (-5, 1)

or

x1 = -5 and y1 = 1

therefore,

y - 1 = 1/4 (x - (-5))

Compute.

y - 1 = 1/4x + 5/4

Multiply both sides by 4 to eliminate fraction for easy computation

4(y - 1) = 4(1/4x + 5/4)

4y - 4 = x + 5

Move 4 to the right and change sign

4y = x + 5 + 4

Compute

4y = x + 9

Then divide both sides by 4 to eliminate the 4 in 4y.

(4y)/4 = (x + 9)/4

y = 1/4x + 9/4

You have it

I hope it helps.

0